Effect of Bioengineering Measures on Runoff, Soil and Nutrient Losses under Cashew Plantations in Western Ghat Region - Manivannan, S; Sikka, A K; Manjunath, B L; Devi, S Priya; Kumar, J Ashok (Journal of Agricultural Engineering, 2007)
A field experiment was conducted on lateritic soil of Western Ghat region in Goa State to study the effect of bioengineering measures viz. Half Moon Terraces + Vetiveria zizanioides + Stylosanthes scabra, continuous contour trench + Vetiveria zizanioides + Stylosanthes scabra, graded trench + Vetiveria zizanioides + Stylosanthes scabra, staggered contour trench + Vetiveria zizanioides + Stylosanthes scabra and semi elliptical trench + Vetiveria zizanioides + Stylosanthes scabra on runoff, soil and nutrient loss and growth of cashew. The study revealed that the bioengineering measures influenced the runoff, soil and nutrient losses and growth parameters of cashew. The reduction of runoff varied from 3.2 to 7.6% of the annual rainfall under different conservation treatments. Minimum runoff(3.5%) and soil loss (3.7 t/ha/year) were recorded under the treatment viz. continuous contour trench + Vetiveria zizanioides + Stylosanthes scabra. Minimum Nitrogen (13.95 kg/ha) and phosphorous (16.53 kg/ha) losses were recorded ill the treatment of continuous contour trenches with Stylosanthes scabra and Vetiveria zizanioides. Growth performance ofcashew was better under the combination of vegetative barriers with continuous contour trenches, graded trenches and staggered contour trenches. Overall, continuous contour trenches with Stylosanthes scabra and Vetiveria zizanioides was found to be the best soil and water conservation treatment among all other bioengineering measures for cashew plantations in Western Ghat region.